The implication of overtime for well-being and desired working hours among office workers: The role of temporal flexibility - Mühl, Arabella; Hartner-Tiefenthaler, Martina; Feuchtl, Silvia (Momentum Quarterly, 2023)
Based on the Job Demands-Resources Model (Demerouti et al. 2001), we argue that overtime work is a job demand that negatively relates to employees’ well-being and increases their desire to reduce their working hours. However, we argue that self-determined temporal flexibility enables individuals to cope with extended working hours. We hypothesized that temporal flexibility weakens the relationships between overtime and the desire to reduce working hours and conducted a survey among 159 Austrian employees who indicated that they did not desire to increase their working hours. In line with prior research, our results show that overtime relates negatively to employees’ reported health, sleep quality, and work-life balance and positively to their desire to reduce actual working hours. Moreover, we found convex relationships between overtime hours and the desired reduction of actual and contractual working hours. Self-determined temporal flexibility was able to buffer the effects of overtime on the desire to reduce contractual working hours, which suggests that self-determined temporal flexibility is a job resource that enables employees to cope with work demands, albeit only when they do not become too intense.
Keywords: Overtime work; workload; temporal flexibility; reduction of working hours